Reconciliation and environmental justice - McGregor, Deborah (Osgoode Digital Commons, 2018)
The conclusion of the Truth and Reconciliation Commission (2015) launched a new chapter in Indigenous-state relationships in Canada. Despite many resulting ‘reconciliation initiatives’, there remains considerable discussion as to what form reconciliation should take and for what end. Reconciliation processes must involve Indigenous peoples from the outset and should be founded on Indigenous intellectual and legal traditions. Indigenous peoples’ conceptions of reconciliation differ markedly from state-sponsored views, particularly the view that reconciliation must be achieved among all beings of Creation, including all living things and entities that broader society does not consider to be alive (e.g. water). Indigenous concepts of reconciliation extend discussions beyond human dimensions to encompass reconciliation with the natural world as a path forward to achieve justice. As such, reconciliation must also include discussion of Indigenous environmental justice, as both Indigenous and non-Indigenous peoples need to heal their damaged relationships with each other and to the land. The Anishinaabe concept of Mino-bimaatisiwin the ‘good life’, or ‘living well’) offers guidance for ensuring that balanced relationships among all beings of Creation are maintained. Concepts such as these could provide significant guidance as we work towards achieving a more sustainable and just society through reconciliation efforts.